The Effectiveness of The Multi-Way Question and Answer Method to Increase Student Activity in Online Lectures - Mardeli Mardeli; Lola Fadilah; Karim Abdillah (AL-ISHLAH: Jurnal Pendidikan, 2023)
The multi-directional question and answer method is one method that can be used to increase student activity in online lectures. The multi-way question and answer method is a way of presenting the material to be studied in the form of questions that must be answered. This research aims to determine the effectiveness of implementing the multi-directional question and answer method to increase student activity in online lectures in child and adolescent development psychology at UIN Surakarta. This research is qualitative in nature and to strengthen the findings descriptive statistical data was used. Data collection was carried out through three steps, namely interviews, observations, and questionnaires in form. The results obtained show that the application of the multi-directional question and answer method in the online lecture process of child and adolescent development psychology at a state islamic university in Surakarta can increase student activity. The indication can be seen from the number of students who asked and also answered questions, as evidenced by the results of the questionnaire, which showed that the indicators for visual activity, listening activity, writing activity and oral activity achieved a presentation above 75% which was in the very good category, while the mental activity indicator was very good. It shows results of 75%.